2014
DOI: 10.1186/1742-2094-11-118
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of ent-Sauchinone on amyloidogenesis via inhibition of STAT3-mediated NF-κB activation in cultured astrocytes and microglial BV-2 cells

Abstract: Backgroundent-Sauchinone is a polyphenolic compound found in plants belonging to the lignan family. ent-Sauchinone has been shown to modulate the expression of inflammatory factors through the nuclear factor-kappa B (NF-κB) signaling pathway. It is well known that neuroinflammation is associated with amyloidogenesis. Thus, in the present study, we investigated whether ent-Sauchinone could have anti-amyloidogenic effects through the inhibition of NF-κB pathways via its anti-inflammatory property.MethodsTo inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 46 publications
(44 reference statements)
4
25
0
Order By: Relevance
“…Studies have also shown that lipopolysaccharide (LPS) can stimulate Aβ deposition [12][13][14], suggesting that neuroinflammation could be a causative contributor in the development and/or progression of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that lipopolysaccharide (LPS) can stimulate Aβ deposition [12][13][14], suggesting that neuroinflammation could be a causative contributor in the development and/or progression of AD.…”
Section: Introductionmentioning
confidence: 99%
“…The STAT3 signaling has been reported to play a critical role in inflammatory responses in the CNS [ 37 ]. STAT3 is activated by phosphorylation at Tyr705, which induces STAT3 dimerization, nuclear translocation, and DNA binding, resulting in the transcription of genes encoding several inflammatory factors [ 37 40 ]. In our study, we observed that astrocytic p-STAT3 was up-regulated after MCAO in vivo and after OGD in vitro, and this effect was reversed by Sino treatment (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of neurodegenerative disorders has increased nowadays and has become one of the most serious health issues worldwide. Neurodegenerative disorders are associated with a higher risk of neurodegenerative diseases, including Huntington's, Alzheimer's and Parkinson's (27,28). Abnormal microglia activation has a crucial role in the development of neurodegenerative disorders, although the exact mechanisms have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%